The Influence of Digital Marketing Product Diversity and Knowledge Sharing on Competitive Advantage with Business Strategy as a Mediation Variable in The Veterinary Clinic Industry in Depok City - Adrianida Irma Saleh,; Sabihaini,; R. Heru Kristanto HC, (Technium Social Sciences Journal, 2024)
This research aims to analyze the influence of digital marketing, product diversity, and knowledge sharing on the competitive advantage of veterinary clinics in Depok City, as well as examining the role of business strategy as a mediating variable in this relationship. The survey method was used to collect data from owners or managers of veterinary clinics spread across Depok City. This research sample consisted of 47 respondents. The results of data analysis using multiple regression show that digital marketing, product diversity and knowledge sharing have a significant positive influence on the competitive advantage of veterinary clinics. Apart from that, business strategy is also proven to mediate the relationship between digital marketing, product diversity, and knowledge sharing with competitive advantage. These findings indicate that digital marketing, product diversity, and knowledge sharing are important factors in influencing the competitive advantage of veterinary clinics. In addition, using the right business strategy can increase the positive impact of these factors. The practical implication of this research is that veterinary clinics in Depok City need to pay attention to and develop digital marketing strategies, expand product diversity, and encourage internal knowledge sharing to increase their competitiveness in the market. Future research could explore other factors that may influence competitive advantage in the context of the veterinary clinic industry.